2012
DOI: 10.1111/j.1600-6143.2012.04138.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Evaluating Performance in Deceased Donation: The Spanish Quality Assurance Program

Abstract: The Spanish Quality Assurance Program applied to the process of donation after brain death entails an internal stage consisting of a continuous clinical chart review of deaths in critical care units (CCUs) performed by transplant coordinators and periodical external audits to selected centers. This paper describes the methodology and provides the most relevant results of this program, with information analyzed from 206,345 CCU deaths. According to the internal audit, 2.3% of hospital deaths and 12.4% of CCU de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 13 publications
1
33
0
2
Order By: Relevance
“…External audits of procurement hospitals in Spain have revealed that 25% of persons in a brain-dead condition are not considered medically suitable organ donors, although some of these medical contraindications are inappropriately established by the donor coordinator or the treating physician (10). While safety of the process is an unquestionable professional standard, an evidence-based analysis of the risks should guide decisions on donor selection at a moment of organ shortage.…”
Section: Nonstandard Risk Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…External audits of procurement hospitals in Spain have revealed that 25% of persons in a brain-dead condition are not considered medically suitable organ donors, although some of these medical contraindications are inappropriately established by the donor coordinator or the treating physician (10). While safety of the process is an unquestionable professional standard, an evidence-based analysis of the risks should guide decisions on donor selection at a moment of organ shortage.…”
Section: Nonstandard Risk Donorsmentioning
confidence: 99%
“…The decrease in the occurrence of events potentially leading to devastating brain injuries as a result of transport and work safety measures, along with improvements in the treatment of neurocritical patients, explain such a decrease in mortality. The extended use of decompressive craniectomies and other neurosurgical interventions has also contributed to a progressive decline in the incidence of brain death, which has evolved from 65 cases pmp in 2001 to <50 pmp during the past years (10).…”
Section: Challenges For the Spanish Donation And Transplantation Systemmentioning
confidence: 99%
“…One study done in Spain comparing ICU with neurosurgery services and ICU without neurosurgery service, showed rate of brain death to be 8% and 13% among all deaths respectively. 24 Another study done in Portugal, showed hospitals with neuro-critical care units having 33% brain death among total number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…15 A real donor was defined as a BD donor entering the operating room and from whom at least one organ was harvested for transplantation. 4,5,16 The BD potential in turn was defined as the proportion of cases diagnosed with BD among the total patients admitted to hospital with GCS < 8.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…3 Brain death has been estimated to represent 2.3% of all in-hospital fatalities and 12.4% of all deaths in the Intensive Care Unit (ICU). 4 Although these indicators are based on retrospective analyses of deaths occurring in critical care settings, they serve as a reference for calculating donation potential in our centers. The quality assurance program of the Spanish National Transplant Organization (Organización Nacional de Trasplantes, ONT), designed to determine the donation potential of critical care units (based on internal and external audits that evaluate the ultimate circumstances in which patients die in such units), retrospectively identifies the ''losses'' of potential donors not identified by the transplant coordinators in real time, and helps to define areas for improvement in the audited hospitals.…”
Section: Introductionmentioning
confidence: 99%